An Analysis of the Interactions between the 5' UTR and Introns in Mitochondrial Ribosomal Protein Genes - Deng, Junchao; Li, Ruifang; Song, Xinwei; Gao, Shan; Peng, Shiya; Tian, Xu (Current Bioinformatics, 2025)
<span class=
Keywords: species evolution